Desulfurization of Zawia Refinery Diesel Using Adsorption Fixed Bed Process - Abdu, Abdulsalam; Faneer, Khalefa A.; Altair, Hadeel; Jammom, Saja; Abdalmolla, Nosiba (International Journal of Environment, Engineering and Education, 2024)
The study focuses on the dynamic modeling of a fixed-bed adsorber for the adsorption of sulfur compounds in diesel fuel. The model considers non-ideal plug flow behavior and velocity variation along the column, providing a more realistic representation of the adsorption process. Additionally, internal mass-transfer resistances due to pore diffusion mechanisms are incorporated into the model. The study investigates adsorption performance by examining different flow rates (5 cc/min, 10 cc/min, 15 cc/min, and 20 cc/min) and inlet concentrations ranging from 586 to 100 ppm. The bed height is constant at 30 cm. The behavior of various parameters, such as bed utilization, breakpoint time, film mass transfer coefficient, and height of the adsorption zone, is analyzed. The results indicate that a sharp front of the breakthrough curve is observed, followed by the broadening of the tail of the breakthrough curve. The breakthrough curve represents the adsorbate concentration in the effluent stream over time. The investigation reveals that a high flow rate of 20 cc/min and a high inlet concentration yield better overall bed capacity utilization for the adsorption system. This means that the bed is more effectively utilized at higher flow rates and higher inlet concentrations, leading to improved adsorption performance. In conclusion, high flow rates and high inlet concentrations are favorable for enhancing the adsorption system's performance in terms of bed utilization. These results provide valuable insights for optimizing the design and operation of fixed-bed adsorbers that remove sulfur compounds from diesel fuel.